The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2020
DOI: 10.1590/s1517-707620200004.1183
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of nano-TiO2 on properties of cementitious mortars

Abstract: This work deals with the effect in fresh and hardened properties of nano-TiO 2 as addition in cement-based mortars. Three commercial nano-TiO 2 powders were characterized by laser granulometry, XRD, FRX, zeta potential, BET and SEM. Two cementitious mortars were produced with nano-TiO 2 , an industrialized and a non-industrialized type; then, these mortars were characterized by flowability, surface roughness, flexural strength and surface fracture. The results showed that the nano-TiO 2 addition reduced the fl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 22 publications
0
8
0
2
Order By: Relevance
“…Such functionalities have the potential to improve the sustainability of construction materials [45]. Furthermore, despite being chemically inert in terms of its potential to directly react during cement hydration [19,24,40,44,45], nano-titanium dioxide can generally improve the mechanical performance and durability, as well as decrease the rigidity of cementitious materials [20,28,31,35,37,44,[51][52][53][54][55][56]. Moreover, the flexural fatigue performance and abrasion resistance of concretes was reported to be remarkably improved with the use of TiO2 nanoparticles [31].…”
Section: Influence Of Incorporation Of Nano-titania Into Cementitious Compositesmentioning
confidence: 99%
See 2 more Smart Citations
“…Such functionalities have the potential to improve the sustainability of construction materials [45]. Furthermore, despite being chemically inert in terms of its potential to directly react during cement hydration [19,24,40,44,45], nano-titanium dioxide can generally improve the mechanical performance and durability, as well as decrease the rigidity of cementitious materials [20,28,31,35,37,44,[51][52][53][54][55][56]. Moreover, the flexural fatigue performance and abrasion resistance of concretes was reported to be remarkably improved with the use of TiO2 nanoparticles [31].…”
Section: Influence Of Incorporation Of Nano-titania Into Cementitious Compositesmentioning
confidence: 99%
“…Moreover, due to its high specific surface area (SSA), nano-titania reduces the workability of the mixture. Such reduction gets greater with increase of nano-TiO2 content in the mixture [5,20,51,55,63,64]. Although much research has been done related to the incorporation of titania nanoparticles into cementitious materials, there is still big lack of information, which necessitates further investigation.…”
Section: Influence Of Incorporation Of Nano-titania Into Cementitious Compositesmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, it was found that various nanomaterials, such as nano-TiO 2 [6,7] and graphene [8,9] could be successfully used to improve the mechanical properties and durability of the mortars [10][11][12]. Nano-TiO 2 has been also proved an excellent photocatalytic material that imparts biocidal, self-cleaning, and smog-abating functionalities when added to cement-based materials [13,14].…”
Section: Introductionmentioning
confidence: 99%
“…Nessa mesma perspectiva, outras áreas da engenharia buscam meios de compatibilizar superfícies por meio de reagentes químicos [7][8][9][10]. Uma necessidade na engenharia de compósitos cimentícios é a utilização de fibras de aço como reforço estrutural [11].…”
Section: Introductionunclassified